The Cambridge handbook of the capability approach - Chiappero Martinetti, Enrica (Cambridge : Cambridge University Press, 2021)
This landmark handbook collects in a single volume the current state of cutting-edge research on the capability approach. It includes a comprehensive introduction to the approach as well as new research from leading scholars in this increasingly influential multi-disciplinary field, including the pioneers of capability research, Martha C. Nussbaum and Amartya Sen. Incorporating both approachable introductory chapters and more in-depth analysis relating to the central philosophical, conceptual and theoretical issues of capability research, this handbook also includes analytical and measurement tools, as well as policy approaches which have emerged in the recent literature. The handbook will be an invaluable resource for students approaching the capability approach for the first time as well as for researchers engaged in advanced research in a wide range of disciplines, including development studies, economics, gender studies, political science and political philosophy.
Title from publisher's bibliographic system (viewed on 12 Nov 2020).
Keywords: Economic development -- Moral and ethical aspects; Values; Freedom; Capabilities approach (Social sciences)